THE ILLOCUTIONARY ACT OF HAZEL GRACE IN THE FAULT IN OUR STARS MOVIE - Septia Elisabeth Nainggolan; Juli Rachmadani Hasibuan (State University of Medan, 2015)
This study deals with Illocutionary Act of Hazel Grace as the main character inThe Fault in Our Stars movie. The objectives of the study was discovered thetypes of Illocutionary Act which were used by Hazel Grace as the main characterand described in what contexts that she used in The Fault in Our Stars movie. Thesubject of this study was The Fault in Our Stars movie and each spoken words orthe conversation by Hazel Grace that were written in The Fault in Our Starsmovie script became the source of the data. The data were collected by browsingand downloading from internet. This study was conducted by using qualitativedescriptive design. The result of analyzing types and the contexts of IllocutionaryAct were used by Hazel Grace as main character such as representatives with34.6% (236 utterances), directives with 24.3% (166 utterances), expressives with22.2% (152 utterances), declaratives with 15.5% (106 utterances) andcommissives with 3.4% (23 utterances) and made representative became the mostdominant type. And representative context was the dominant context because TheFault in Our Stars movie used first person, main character’s point of view fromperspective of the main character that Hazel Grace used like informing,describing, sharing, believing, stating a fact, assuming, predicting and alsocomplaining which make her like a narrator in that movie because she informs,describes, shares about her diseases, her interests, her thought also about life oreverything, and what she believe by herself.